2018
DOI: 10.1111/cch.12549
|View full text |Cite
|
Sign up to set email alerts
|

Are the health needs of young people with cerebral palsy met during transition from child to adult health care?

Abstract: BackgroundThe transition from child to adult health care is a particular challenge for young people with cerebral palsy, who have a range of needs. The measurement of reported needs, and in particular unmet needs, is one means to assess the effectiveness of services.MethodsWe recruited 106 young people with cerebral palsy, before transfer from child services, along with their parents to a 3‐year longitudinal study. Reported needs were measured with an 11‐item questionnaire covering speech, mobility, positionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 32 publications
2
57
3
1
Order By: Relevance
“…This review reveals that current services are often ill-prepared to respond to these multifaceted health needs of young people with ID at the point of transition from paediatric to adult health care wider evidence pointing to poor experience of health transitions for young people with a range of chronic conditions (Heery, Sheehan, While, & Coyne, 2015;Singh & Tuomainen, 2015;Solanke, Colver, & McConachie, 2018) and a lack of research to evaluate focussed interventions (Campbell et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This review reveals that current services are often ill-prepared to respond to these multifaceted health needs of young people with ID at the point of transition from paediatric to adult health care wider evidence pointing to poor experience of health transitions for young people with a range of chronic conditions (Heery, Sheehan, While, & Coyne, 2015;Singh & Tuomainen, 2015;Solanke, Colver, & McConachie, 2018) and a lack of research to evaluate focussed interventions (Campbell et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] Disabling conditions such as cerebral palsy give rise to symptoms including pain and spasticity which may not be adequately addressed during transition. 9 Few young adults with neurodevelopmental disorders such as autism spectrum disorder (ASD) attain their potential for employment, relationships and participation in society. 10,11 Such problems are recognised internationally.…”
Section: Importance Of Transitionmentioning
confidence: 99%
“…In the present study, immediate families were identified as the most important persons for adults with CP, since many of them still lived with their pa- e160 Products and technology of land development 20 (15.9) e575 General social support services, systems and policies 20 (15.9) www.medicaljournals.se/jrm rents or needed support from their family. The experts also regularly commented on "Services, systems and policies", of which health services were the most often indicated, showing the awareness of the experts of the need to continue healthcare services for persons with CP during their transition to adulthood and thereafter (21,25,26). Notably, the experts considered most Environ mental factors as both supportive and hindering factors for adults with CP, except for "Societal attitudes", which was indicated only as a hindering factor.…”
Section: Discussionmentioning
confidence: 99%